Dog-Assisted Therapy for Children and Adolescents With Fetal Alcohol Spectrum Disorders a Randomized Controlled Pilot Study - Vidal, Raquel; Vidal, Laura; Ristol, Francesc; Domènec, Eva; Segú, Marta; Vico, Cristina; Gomez-Barros, Núria; Ramos-Quiroga, Josep Antoni (Frontiers in Psychology, 2020)
Objective: The rationale of this study was to evaluate the efficacy of Dog Assisted Therapy (DAT) in children and adolescents with Fetal Alcohol Spectrum Disorder (FASD). Method: We conducted a randomized, rater-blinded, controlled pilot trial in a cohort of 33 children and adolescents with FASD. Participants were randomly assigned either to DAT group (n=17) or Treatment as Usual (TAU control group) (n=16). Results: Of the initial 39 participants enrolled, 33 completed treatment. A mixed-effects model analysis revealed that participants who were assigned to the DAT group experienced significantly improvements on social skills (SSIS-P Social Skills: p=0.02, d=0.8), reductions on externalizing symptoms (CBCL Externalizing: p=0.03; d=0.56), and lower scores on FASD severity (CGI-S Clinician: p=0.001, d=0.5). Conclusions: DAT is a promising adjunctive treatment for children and adolescents with FASD.